Association of longevity with type traits, milk yield and udder health in Holstein cows - Stefani, Gabriela [UNESP]; El Faro, Lenira; Santana Júnior, Mário Luiz; Tonhati, Humberto [UNESP] (Elsevier, 2018)
Genetic associations were estimated between 305-day cumulative milk yield (MY305) and maximum somatic cell score (SCS) in the first lactation, stayability in the herd at 60 months of age (Stay60), and linear udder and feet and legs traits. First-lactation records of Holstein cows reared in intensive production systems in Brazil were used. The (co)variance components were estimated using a Bayesian approach. The heritability estimates were 0.24 ± 0.02, 0.08 ± 0.02 and 0.09 ± 0.03 for MY305, SCS and Stay60, respectively. The heritabilities of the linear traits ranged from 0.16 to 0.39 for udder traits and from 0.13 to 0.21 for feet and legs traits. Stay60 showed genetic correlations of -0.25 ± 0.12 with MY305, 0.11 ± 0.20 with SCS, 0.33 ± 0.16 with rear teat placement, and -0.47 ± 0.13 with a rear legs-side view. It is possible to promote early genetic gains in the longevity of animals by selecting for moderately correlated traits to obtain a good set of feet and legs, as well as well-positioned teats of medium length. Extreme milk yields are associated with a reduction in Stay60. SCS in the first lactation has practically no influence on Stay60. The maximum selection efficiency will be achieved by selecting directly by Stay60.
Keywords: Dairy cattle; Genetic correlation; Heritability; Threshold model